Evaluating the nonlinear dynamic stiffness of rail pad using finite element method / Mohamad Hazman Halim ... [et al.] - Halim, Mohamad Hazman; Abdul Wahab, Abdul Malek; Hadi, Muhamad Sukri; Ibrahim, Azmi; Mohamad Noor, Noraishah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Unwanted vibration and noise from railroads have a significant negative impact on the environment, causing damage to roads, buildings, and other structures. To mitigate this condition, rail pads have been installed as dampers to lessen the impact of vibration and shock on the railway track. The rail pad is made of a polymeric substance having nonlinear properties. This research examined the dynamic stiffness of rail pads made of thermoplastic elastomers (TPEs). ANSYS software was used to estimate the impact of temperature, toe load, and frequency under dynamic loading. The three-dimensional (3D) finite element model (FE) was created based on hyperelastic theory. The dynamic stiffness of the interlayer decreases with increasing temperature. For the effect of peak load and frequency, both parameters were directly proportional to dynamic stiffness. An increase in either parameter results in a stiffening of the interlayer. Frequency has the least effect on the dynamic stiffness of the track bed compared to temperature and peak load, with the average percentage difference between high and low being 28.31%, 55.57%, and 21.9%, respectively.